Tinjauan Yuridis Tindak Pidana Pemerkosaan terhadap Anak Kandung : Studi Kasus di Pengadilan Negeri Sei Rampah Nomor 511 /Pid.Sus/ 2022 Pn Srh - Himawan Azri Lubis; Bonanda Japatani Siregar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Rape is a criminal act by means of violence, threats and forcing the will on others, to commit an act that violates the rules, rape is often committed by someone by forcing others to have intercourse with threats and violence. In rape, many become victims, where almost all victims lack the courage to defend themselves so that it is easy for someone to commit rape. As in article 285 of the Criminal Code. The type of research used is normative juridical and empirical juridical. Normative juridical research is legal research that places law as a building of a norm system. The norm system in question is regarding the principles, norms, rules of laws and regulations, agreements and doctrines (teachings). This research was conducted on secondary data such as laws and regulations, scientific journals, law books related to the law of cooperation agreements and agencies. While empirical juridical research is research that has an object of study regarding community behavior. The behavior of the community studied is behavior that arises as a result of interacting with the existing norm system. The interaction emerged as a form of public reaction to the implementation of a positive legal provision and can also be seen from the behavior of the community as a form of action in influencing the formation of a positive legal provision. Empirical legal research in writing this thesis was conducted through direct interviews with the Sei Rampah District Court, Serdang Bedagai Regency. Research Results A. Imposition of sanctions on perpetrators of rape in the decision of the Serdang Bedagai District Court Number 511 / Pid.Sus / 2022 Pn Srh. Sentencing the Defendant therefore to imprisonment for 14 (fourteen) years and a fine of Rp1,000,000,000.00 (one billion rupiah) with the provision that if the fine is not paid it is replaced with imprisonment for 2 (two) months; B. Regulation of criminal acts of indecency in laws and regulations. Article 281 of the Criminal Code Threatened with a maximum imprisonment of 2 years and 8 months or a maximum fine of Rp4.5 million: C. Obstacles faced in protecting victims of indecency against women and steps. The obstacles experienced are in the form of a protracted legal process (undue delay), evidence, the absence of articles regulating certain sexual crimes, intimidation from the perpetrator, and lack of support from the victim's closest environment.